Analisis Kemampugaruan Batuan Berdasarkan Metode Seismic Pada Penambangan Batupasir Provinsi Kalimantan Timur : Analisis Kemampugaruan Batuan - Bayu Indra Dermawan; Agus Winarno; Shalaho Dina Devy; Tommy Trides; Revia Oktaviani (Retii, 2024)
In mining activities, high risk is one of the main aspects that must be anticipated, especially regarding the geomechanical complexity of the rocks being excavated. Selecting the right excavation method can greatly impact operational efficiency and safety. In this context, direct digging, ripping, and blasting are the three main options, tailored to the characteristics of the rock.To determine the most suitable method, a rock rippability study is essential. This study can be conducted using direct or indirect methods. In this research, the seismic method was used to assess rock strength based on the seismic wave velocity, which was recorded at 1437.80 m/s. This value serves as a reference for selecting appropriate equipment for ripping activities.Given these characteristics, the recommended equipment for ripping is the D8T/D8R dozer from Caterpillar or the D275A/D275AX dozer from Komatsu. This equipment choice is based on its capability to handle rocks with strength levels reflected by the measured seismic wave velocity.